2022
DOI: 10.1002/aoc.6634
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of silver nanoparticles on Cu‐BTC metal–organic framework under the influence of reaction conditions and investigation of their antibacterial activity

Abstract: In this work, silver nanoparticles were loaded on Cu‐BTC metal–organic framework (MOF) by chemical reduction method in the presence of NaBH4. Characterization of structures was performed by FT‐IR, XRD, SEM, TEM, ICP‐OES, N2 adsorption–desorption isotherm, and TGA techniques. Changes in the reaction conditions, especially the used solvent, in the synthesis of the compounds were investigated, and it was found that the amount of silver loaded, size, distribution, and morphology of the particles depended on it. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
(88 reference statements)
1
12
0
Order By: Relevance
“…Therefore, Ag@ZIF-7 can compete with silver-containing copper frameworks in the antibacterial properties. 65 In another study that was carried out on the loading of silver nanoparticles on titanium oxide (TiO 2 ) and zinc oxide (ZnO), it was shown that the maximum ZOI of synthesized materials is lower than the ZOI reported in this study, which indicates that Ag@ZIF-7 can serve as a highly suitable carrier for silver nanoparticles capable of inhibiting bacteria through the release of both Zn 2+ and Ag + ions. In addition, in cases such as loading on zinc oxide and titanium oxide nanoparticles, the presence or absence of LED irradiation can impact the final result and can affect the amount of antibacterial activity of the products; on the other hand it does not apply to ZIF-7, and Ag@ZIF-7 shows good antibacterial properties under both conditions.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Therefore, Ag@ZIF-7 can compete with silver-containing copper frameworks in the antibacterial properties. 65 In another study that was carried out on the loading of silver nanoparticles on titanium oxide (TiO 2 ) and zinc oxide (ZnO), it was shown that the maximum ZOI of synthesized materials is lower than the ZOI reported in this study, which indicates that Ag@ZIF-7 can serve as a highly suitable carrier for silver nanoparticles capable of inhibiting bacteria through the release of both Zn 2+ and Ag + ions. In addition, in cases such as loading on zinc oxide and titanium oxide nanoparticles, the presence or absence of LED irradiation can impact the final result and can affect the amount of antibacterial activity of the products; on the other hand it does not apply to ZIF-7, and Ag@ZIF-7 shows good antibacterial properties under both conditions.…”
Section: Resultsmentioning
confidence: 51%
“…This characteristic of metal–organic frameworks allows them to have a regulated release as antibacterial agent reservoirs or as carriers. 65 As seen clearly from the graphs, the first concentration of released Ag + ions is higher than that of Zn 2+ ions, even though the sampling was done at the same time and after the same period. The reason is that the released Zn 2+ ions are the result of the destruction of the framework, while the released Ag + ions can be attributed to the surface-adsorbed silver nanoparticles.…”
Section: Resultsmentioning
confidence: 87%
“…The sizes of NPs and mesopores increased with the addition of 20 wt % Ag NPs, and some aggregates attached onto the surface of the Cu-BTC. This finding indicated that adding Ag NPs can affect the structure and morphology of Cu-BTC Figure f reveals that the Ag element marked with purple color was homogeneously dispersed throughout the matrix of Cu-BTC nanocrystals, as for the nucleation effect of Ag NPs.…”
Section: Resultsmentioning
confidence: 87%
“…This finding indicated that adding Ag NPs can affect the structure and morphology of Cu-BTC. 30 Figure 2f reveals that the Ag element marked with purple color was homogeneously dispersed throughout the matrix of Cu-BTC nanocrystals, as for the nucleation effect of Ag NPs. With increased content of Ag NPs to 40 wt %, the pores enlarged and some macropores produced were 200 nm in size (Figure 2g).…”
Section: Resultsmentioning
confidence: 93%
“…Very important compounds formed by carboxylic acids are metal–organic frameworks (MOFs). These were mostly applied for their physical properties but they were also studied as antibacterial agents or drug transporters [ 9 , 10 , 11 , 12 , 13 , 14 ]. Zinc carboxylates can be utilized as precursors for zinc oxide nanoparticles and are studied for their biological activities [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%